The Impact of Wearing a Face Mask during the COVID-19 Pandemic on Temporomandibular Joint: A Radiological and Questionnaire Assessment - Zuhour, Moath; Ismayilzade, Majid; Dadacı, Mehmet; Ince, Bilsev (Indian Journal of Plastic Surgery, 2022)
Aim Several health problems have been reported to be triggered or facilitated by prolonged mask usage during the coronavirus disease 2019 (COVID-19) pandemic. While wearing a face mask, people tend to push their jaws forward and downward in a repetitive manner to hold their masks in the right position; these jaw motions may induce temporomandibular joint disorder (TMD). In this study, we aimed to investigate these repetitive jaw movements while wearing face masks and their effects on TMD.Patients and Methods Patients who applied with TMD signs between June 2020 and May 2021 were evaluated prospectively. A survey using a questionnaire was conducted to define patients with TMD that caused only by mask-related repetitive jaw movements. Demographic data (age and gender), mean duration of daily mask usage, mask type, and magnetic resonance imaging results were recorded.Results Prolonged daily mask usage (≥8 hours/day) was significantly higher in patients with mask-related habits (group a) with a rate of 40.4% (p ≈ 0.001). Also, in this group, the disc displacement with reduction rate (54.6%) was higher compared with other groups (p ≈ 0.010). On the contrary, patients with no underlying risk factor (group c) showed an unexpected high osteoarthritis rate (p ≈ 0.029).Conclusions In this study, we demonstrate that correcting the position of a face mask by repetitive jaw movements can increase the occurrence of TMD. Informing individuals wearing face masks about the risk of TMD and the importance of choosing the appropriate mask size according to the face shape are important issues to be addressed in the near future.
Keywords: COVID-19 pandemic; face mask; temporomandibular disorder; Surgical mask